Preliminary testing results of a diaphragm FPSE - Ghozzi, Salem; Boukhanouf, Rabah (2016)
The paper presents design and preliminary testing results of a Free Piston Stirling Engine (FPSE) prototyp operating at low temperature heat sources. The main focus of this work is to demonstrate the construction of the displacer using flexure bellows as a mechanical supporting spring and as a working fluid seal. The power piston, on the other hand, is made of a planar elastomer material in the shape of a disk with a suitable mechanical elasticity, rigidity, and thermal properties to support the range of operating temperatures. A small prototype of the FPSE was built and tested at operating temperature of under 200 oC. The measured operating frequency was 15 Hz, a reciprocating stroke of 8mm and operating pressure close to atmospheric pressure. The prototype was equipped with instruments to measure all the operating parameters. The power output was measured from the p-v diagram using a two-channel oscilloscope. The preliminary results demonstrated the operation concept and reliable start up, but further improvements will be needed to fine tune the reciprocating components and reduce mechanical friction.